The Study of Maximum Phonation Time of Elderly in Nonthaburi Province: The Study of Maximum Phonation Time of Elderly in Nonthaburi Province - จันทรวรรณ แก้วไสว, (Thai Journal of Otolaryngology Head and Neck Surgery, 2023)
บทคัดย่อ (Abstract) การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาค่าเกณฑ์ปกติของค่าแม็กซิมั่มโฟเนชั่นไทม์ในผู้สูงอายุไทยที่อาศัยอยู่ในจังหวัดนนทบุรี จำนวน 140 คน แบ่งออกเป็น 3 ช่วงอายุ ได้แก่ อายุ 60-69 ปี, 70-79 ปี และ 80-89 ปี การทดสอบทำโดยให้ผู้เข้าร่วมวิจัยสูดหายใจเข้าให้ลึกแล้วออกเสียง“อา”, “อู” และ “อี” ให้นานที่สุดเท่าที่จะทำได้ด้วยความดังปกติ ผลการศึกษาพบว่าค่าเฉลี่ยของค่าแม็กซิมั่มโฟเนชั่นไทม์ของทุกช่วงอายุเท่ากับ 14.98, 17.25, 17.42 วินาที (เสียง อา อู และอีตามลำดับ) และค่าเฉลี่ยของค่าแม็กซิมั่มโฟเนชั่นไทม์ที่ได้ในแต่ละช่วงอายุไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติ (p>0.05) The purpose of this study was to obtain normative data of maximum phonation time in 140 Thai elderly living in Nonthaburi province. The subject was divided into three age groups: 60-69 years, 70-79 years and 80-89 years. The subject was instructed to take a deep breath and to sustain the vowel “aa”, “uu” and “ii” as long as possible at a normal volume. The results of this study showed that the means of maximum phonation time in all age groups were 14.98, 17.25, 17.42 seconds (/aa/, /uu/, and /ii/, respectively). There was a non-significant difference in maximum phonation time between all age groups of subjects (p>0.05). คำสำคัญ (Key words) maximum phonation time, Elderly